Phosphorylation of the lipid A region of meningococcal lipopolysaccharide: identification of a family of transferases that add phosphoethanolamine to lipopolysaccharide. - Cox, A; Wright, J; Li, J; Hood, D; Moxon, E; Richards, J (2003)
A gene, NMB1638, with homology to the recently characterized gene encoding a phosphoethanolamine transferase, lpt-3, has been identified from the Neisseria meningitidis genome sequence and was found to be present in all meningococcal strains examined. Homology comparison with other database sequences would suggest that NMB1638 and lpt-3 represent genes coding for members of a family of proteins of related function identified in a wide range of gram-negative species of bacteria. When grown and isolated under appropriate conditions, N. meningitidis elaborated lipopolysaccharide (LPS) containing a lipid A that was characteristically phosphorylated with multiple phosphate and phosphoethanolamine residues. In all meningococcal strains examined, each lipid A species contained the basal diphosphorylated species, wherein a phosphate group is attached to each glucosamine residue. Also elaborated within the population of LPS molecules are a variety of "phosphoforms" that contain either an additional phosphate residue, an additional phosphoethanolamine residue, additional phosphate and phosphoethanolamine residues, or an additional phosphate and two phosphoethanolamine residues in the lipid A. Mass spectroscopic analyses of LPS from three strains in which NMB1638 had been inactivated by a specific mutation indicated that there were no phosphoethanolamine residues included in the lipid A region of the LPS and that there was no further phosphorylation of lipid A beyond one additional phosphate species. We propose that NMB1638 encodes a phosphoethanolamine transferase specific for lipid A and propose naming the gene "lptA," for "LPS phosphoethenolamine transferase for lipid A."